The Role of the Teacher in Improving Character in the Learning Discipline of Primary School Students - Salsabila Nasution, Hanmelva; Sagita, Nesa (International Journal of Students Education, 2024)
This research aims to improve disciplined character to realize students’ personal resilience, which is the right way to instill character values in the younger generation in order to create a generation with character and integrity. Teachers always emphasize students to be disciplined and have good personalities in facing challenges and obstacles that weaken personal resilience, to arrive at school on time, not to cheat, to wear uniforms according to the prescribed rules, to be obedient in words and actions. Improving disciplined character to realize students’ personal resilience or developing student character is the main alternative in producing students who are in accordance with the values of Pancasila. The research method used is literature study, research shows that improving the disciplined character of elementary school students can be instilled through habituation and example by a teacher with the aim of educating and equipping students to have good behavior and morals for themselves, society and the surrounding environment. Habituation can become attitudes and behavior as well as character that is automatic and will become a noble personality in students and example is used to instill moral and social values in children. It is important to instill discipline character education from an early age so that in the future children can become the nation’s successors who have competent morals and behavior and become human resources with good character. These two aspects are carried out sustainably and consistently, not only at school but also optimized in the family environment, considering that students spend more time at home than they do at school. The appearance of character education turns out to be able to educate students who are superior not only in the realm of knowledge, emotionally intelligent, but also strong in personality.